Home security system using face recognition - Syed Syafiq, Syed Alias; Nur Shamsiah, Abdul Rahman; Anis Farihan, Mat Raffei (2021)
This is a Home Security System that focuses on using face recognition. The system is divided into two main parts which are an Android application and Raspbery Pi module. Using the Home Security System application, the user will be able to sign up, sign in, reset password, upload face images (for face recognition), retrieve uploaded images, retrieving door status and motion detection history and view CCTV footage. Raspberry Pi module is equipped with a camera module (face recognition purpose), passive infrared (PIR) motion sensor, door sensor and solenoid door lock.